Exploring the Knowledge Map of Green Entrepreneurship through Bibliometric and Co- Word Mapping Analysis Word Mapping - Loso Judijanto; Ardi Azhar Nampira (Westscience Press, 2025)
Green entrepreneurship has gained prominence as a transformative approach to addressing environmental challenges while promoting economic growth. Despite its growing scholarly appeal, the field remains fragmented with diverse interpretations and thematic overlaps. This study employs a bibliometric and co-word mapping analysis to explore the intellectual structure, thematic evolution, and emerging trends in green entrepreneurship literature. Drawing data from the Scopus database and analyzing it using VOSviewer, we identified key authors, collaboration networks, influential countries, and conceptual clusters shaping the field. Central themes include sustainable development, innovation, green economy, and entrepreneurship education. Temporal mapping reveals a recent shift toward educational and capability-based approaches, particularly post-2021. The study highlights the need for deeper theoretical integration, broader regional representation, and enhanced collaboration across disciplines and geographies. These findings provide a comprehensive knowledge map to guide future research, policy formulation, and entrepreneurial practices aligned with global sustainability goals.